An L-threonine aldolase for asymmetric synthesis of β-hydroxy-α-amino acids. (23rd November 2020) - Wang, Li-Chao; Xu, Lian; Xu, Xin-Qi; Su, Bing-Mei; Lin, Juan
Highlights: Mining a L-threonine aldolase from Actinocorallia herbida with robust activity. Different types of aromatic aldehydes exert a significant influence toward AhLTA. The amounts of 4-methylsulfonyl benzaldehyde affect the stereoselectivity of AhLTA. A possible regulation mechanism was put forward in this work. Abstract: L-threonine aldolase (LTA) is a PLP-dependent enzyme that can reversibly catalyze aldol reaction of glycine and acetaldehyde to produce β -hydroxy- α -amino acids. In the present work, a putative lta gene from Actinocorallia herbida (AhLTA) was mined and over-expressed in Escherichia coli BL21 (DE3). The substrate spectrum assay indicated that AhLTA only used glycine as donor substrate and tolerated a wild range of aromatic aldehydes as acceptor substrates. It was found that the type and position of substituents in the aromatic aldehydes exerted a significant impact on the activity and stereoselectivity at β -carbon of AhLTA. Among those substrates, AhLTA could catalyze glycine and 4-methylsulphonyl benzaldehyde (14a ) to produce L- threo -4-methylsulfonylphenylserine ((2 S, 3 R )-14b ) with high conversion (94.4%) and moderate stereoselectivity (19% de ). By conditional optimization, the de value of (2 S, 3 R )-14b was improved to 61% and the conversion was 75%. Taken together, our study suggested that AhLTA might be a promising catalyst for producing chiral β -hydroxy- α -amino acids.